Quality of life in patients with psoriasis - Włodarczyk, Julita; Knyszyńska, Anna; Lubkowska, Anna (Journal of Education, Health and Sport, 2019)
Background: Psoriasis is a chronic autoimmune disease. It is characterized by the occurrence of periods of exacerbation and remission. Symptoms appear in the second or third decade of life. There are many types of psoriasis, such as plaque, inverse, erythroderma psoriasis and specific parts of the body. Another form of pustular psoriasis is. There is also psoriatic arthritis, which is manifested by inflammation of the articular tissues. Various methods of treatment that are dependent form of the disease and location of lesions. Additionally, to relieve lesions uses physical procedures. Psoriasis as a chronic disease can affect quality of life. Aim of study: The aim of the study was to analyze the impact of psoriasis on quality of life and overall spheres such as psychology, physical fitness and meeting the social roles of patients. Materials and methods: The study included 466 people with psoriasis including 370 women and 96 men. The sample was classified by adults, regardless of place of residence and time since diagnosis. 70% of respondents were in the group of 18-40 years. Anonymous diagnostic survey conducted over the internet using a questionnaire SKINDEX-29. Results: Patients assessed their quality of life as good. Variables such as gender, age, BMI or the time of diagnosis does not differentiate the assessment of quality of life. Patients assessed their worst quality of life in the psychological aspect. During the analysis did not show any statistical significance in the comparison of the data obtained. Conclusions: Psoriasis does not reduce the overall quality of life of patients and has no significant impact on the various aspects: psychological, physical, psychosocial functioning. There is no relationship between gender, age, BMI, duration of the disease and the overall quality of life. Used a questionnaire is not a reliable method for testing the quality of life of patients with psoriasis.